2017
DOI: 10.1128/iai.00552-16
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein Kinase 2 Signaling Shapes Macrophage Plasticity in Aggregatibacter actinomycetemcomitans-Induced Bone Loss

Abstract: Aggregatibacter actinomycetemcomitans is associated with aggressive periodontal disease, which is characterized by inflammation-driven alveolar bone loss. A. actinomycetemcomitans activates the p38 mitogen-activated protein kinase (MAPK) and MAPK-activated protein kinase 2 (MK2) stress pathways in macrophages that are involved in host responses. During the inflammatory process in periodontal disease, chemokines are upregulated to promote recruitment of inflammatory cells. The objective of this study was to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…An increase in resorption pits due to osteoclast activity was observed in calvariae treated with A.a, confirming this as a viable model for periodontal disease [33]. Staining for tartrate resistant acid phosphatase (TRAP) and F4/80 marked the area in the calvarial sections most active with inflammatory infiltration.…”
Section: Kdm4b and Kdm4e Protein Abundance Is Increased In Areas Of Psupporting
confidence: 53%
See 2 more Smart Citations
“…An increase in resorption pits due to osteoclast activity was observed in calvariae treated with A.a, confirming this as a viable model for periodontal disease [33]. Staining for tartrate resistant acid phosphatase (TRAP) and F4/80 marked the area in the calvarial sections most active with inflammatory infiltration.…”
Section: Kdm4b and Kdm4e Protein Abundance Is Increased In Areas Of Psupporting
confidence: 53%
“…To determine whether KDM4B inhibition could be used as a therapeutic strategy to manage periodontal disease, we first demonstrated that the abundance of KDM4B protein is significantly increased in areas of inflammatory infiltrate marked by increased F4/80+ macrophage cells and increased tartrate resistant acid phosphatase (TRAP)+ osteoclastic cells following live A.a. subcutaneous injection into murine calvariae (Figure 1(a)) [36]. The murine genome does not express KDM4E [37], leading us to believe that the ML324-induced immunomodulatory effect is entirely dependent on KDM4B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of nuclear β‐catenin can inhibit the noncanonical Wnt pathway, leading to increased proliferation but reduced osteogenic differentiation of periodontal ligament stem cells . ITGAL (Integrin Subunit Alpha L, also known as LFA‐1A, CD11A; gene ID: 3683) was shown to be upregulated in periodontitis and encoded the integrin α L chain of the integrin lymphocyte function‐associated antigen‐1 (LFA‐1/CD11a). LFA‐1/CD11a, a key immunoregulatory cytokine, has been suggested to play an important role in the pathogenesis of periodontal disease, possibly by T‐cell recruitment and retention in the gingival tissue .…”
Section: Discussionmentioning
confidence: 99%
“…Aggregatibacter actinomycetemcomitans oral infection, in association with periodontal disease, can also lead to bone loss due to the inflammatory process. Recently, it has been shown that A. actinomycetemcomitans infection activates stress pathways in macrophages and upregulates chemokine signaling during inflammation and osteoclastogenesis . Despite recent evidence regarding A. actinomycetemcomitans ‐induced bone loss and proinflammatory mechanisms, there is still limited information on A. actinomycetemcomitans invasion and its systemic pathogenesis.…”
Section: Introductionmentioning
confidence: 99%